Blastocystis: Isolation, Xenic Cultivation, and Cryopreservation. Issue 1 (18th November 2016) - Clark, C. Graham; Stensvold, C. Rune
Abstract: Blastocystis is an intestinal parasite that is very easily isolated in culture from fresh stool samples. In fact, the parasite grows so readily in culture that short‐term in vitro culture is sometimes used as a diagnostic tool in the absence of DNA‐based methods. While axenizing Blastocystis cultures remains a significant challenge, the parasite can be propagated for several months in the presence of metabolically active bacteria (xenic culture). Hence, culture can be used for maintaining live Blastocystis strain libraries. This enables the production of a stable resource of reference material, which for instance can be used for DNA‐based assays and research. Blastocystis isolates can also be cryopreserved with a view to reestablishing them in culture. Here, we provide protocols for xenic in vitro culture and cryopreservation of Blastocystis . © 2016 by John Wiley & Sons, Inc.